Perbedaan Kenaikan Berat Badan Bayi yang Diberikan Stimulasi Oral Motor dan Tummy Time - Farida Ayu Munika Irianty; Titi Maharrani; Astuti Setiyani; Tatarini Ika Pipitcahyani (Jurusan Kebidanan Politeknik Kesehatan Kemenkes Surabaya, 2023)
The baby`s weight begins to experience growth disorders at the age of 3 months, and continues to decrease until the age of 12 months. The purpose of this study was to determine the difference in weight gain of infants who were given oral motor stimulation and tummy time. This study used a pre-test post-test control group design. This is a design that performs a pre-test before being given treatment, as well as conducting a posttest after each group is given treatment and will show that there is a treatment that produces a one-way effect.Based on the results of the two different test averages in this study, it was found that the average weight gain of babies who were given oral motor stimulation was higher than the average weight gain of babies who were given tummy time stimulation with a ρ-value of 0. This means that there is an influence of oral motor stimulation on infant growth at the Wonokusumo Health Center. All respondents totaling 70 babies aged 10-28 days had normal weight according to age, namely the average weight before being given oral motor stimulation was 3,198.943 grams, the average after being given tummy time stimulation was 3,748. All respondents experienced an average weight gain of 549.09 grams on tummy time. There was a significant difference between the baby's weight gain given oral motor stimulation and tummy time. It is necessary to do oral motor stimulation to increase body weight in infants, and there is no growth disturbance.